Budget impact of incorporating one instillation of hexaminolevulinate hydrochloride blue‐light cytoscopy in transurethral bladder tumour resection for patients with non‐muscle‐invasive bladder cancer in Sweden. (29th October 2015) - Rose, James B.; Armstrong, Shannon; Hermann, Gregers G.; Kjellberg, Jakob; Malmström, Per‐Uno
Abstract : Objectives: To explore the cost impact on Swedish healthcare of incorporating one instillation of hexaminolevulinate hydrochloride (HAL) blue‐light cystoscopy into transurethral resection of bladder tumour (TURBT) in patients with suspected new or recurrent non‐muscle‐invasive bladder cancer (NMIBC). Materials and Methods: A decision tree model was built based on European Association of Urology guidelines for the treatment and management of NMIBC. Input data were compiled from two recent studies comparing recurrence rates of bladder cancer in patients undergoing TURBT with either the current standard of care (SOC) of white‐light cystoscopy, or with the SOC and HAL blue‐light cystoscopy. Using these published data with clinical cost data for surgical and outpatient procedures and pharmaceutical costs, the model reported on the clinical and economic differences associated with the two treatment options. Results: This model demonstrates the significant clinical benefits likely to be observed through the incorporation of HAL blue‐light cystoscopy for TURBT in terms of reductions in recurrences of bladder cancer. Analysis of economic outputs of the model found that the use of one instillation of HAL for TURBT in all Swedish patients with NMIBC is likely to be cost‐neutral or cost‐saving over 5 years relative to the current SOC of white‐light cystoscopy. Conclusions: The results of this analysis provide additional health economic rationale for the incorporation of a single instillation of HAL blue‐light cystoscopy for TURBT in the treatment of patients with NMIBC in Sweden.